LISZT - PORTRAIT OF A MUSICIAN. “DANTE SYMPHONY” - MARINESCU, Alexandra (Studia Universitatis Babes-Bolyai Musica, 2016)
It is well known the fact that Liszt’s programmatic music does not describe something concrete but rather suggests the feelings triggered by a certain action, theme, landscape or artwork. One of the first statements about Liszt’s intention of writing the Dante Symphony exists in a letter addressed to Richard Wagner, in which the composer confessed: “Like Virgil led Dante, you showed me the way trough the mysterious regions of a lively world of sounds. I say to you wholeheartedly: Tu sei lo mio maestro, e il mio autore – and I dedicate this work to you with all my everlasting love, Weimar – Ostern – 1850. Yours, F. Liszt”[1] In the same letter the author adds, “and if you do not disapprove, I will encrypt your name”[2]. This study aims to reflect the way in which the composer identifies himself with the main character of the Symphony, transcending this journey of creation further than reflected in his other works, in this way transforming the whole opera into an allegoric self portrait. The Symphony presents the protagonist Liszt-Dante starting a fascinating and at the same time terrifying journey through Inferno-Purgatorio and Paradiso, reflecting, probably more than in any other work of his that every note is like a confession of his own personal religious beliefs. [1] Correspondence between Wagner, Liszt, II, 7,1, cf. Raabe, Peter – Vorwort Dante-Symphonie, Verlag von Breitkopf & Härtel, Leipzig, Berlin, Brüssel, 1921, p. 3 [2] Ibid.